PENGUATAN KOMPETENSI CALON GURU EKONOMI MELALUI PENINGKATAN KEILMUAN DAN PROFESIONAL DALAM MATA KULIAH AKUNTANSI - Oktaria, Merisa; Nugraha Putra, Kharisma; Hidayati (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
Abstract: This community service activity aims to improve the academic and professional competencies of prospective economics teachers by strengthening their understanding of accounting courses. The target participants are students of the Economics Education Study Program, Faculty of Teacher Training and Education, Universitas Palangka Raya. The activity was conducted online via the Zoom Meeting platform for five weeks, from February 2 to March 6, 2025. The implementation methods included interactive material delivery and group discussions. The materials provided focused on strengthening the basic concepts of accounting and contextual teaching strategies. The results showed an improvement in participants’ understanding of accounting material. Participants also demonstrated high enthusiasm in practicing innovative online learning. This activity is expected to support the readiness of students as competent economics educators who are relevant to the current needs of the education sector.